1985
DOI: 10.1139/y85-167
|View full text |Cite
|
Sign up to set email alerts
|

Action of insulin modulated by pertussis toxin in rat adipocytes

Abstract: We studied the effect of pertussis toxin (PT) treatment on the ability of insulin to inhibit lipolysis and to stimulate glucose oxidation in isolated rat adipocytes. In cells maximally modified by PT (100% ADP ribosylation of a 41-kdalton protein in membranes), the ability of insulin to inhibit lipolysis stimulated either by PT alone or in combination with a catecholamine was abolished. In cells wherein ADP ribosylation was submaximal (about 67% modification), a small but variable antilipolytic action of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Lutterel et al [18] found that insulin promotes guanine nucleotide-binding to the membranes of BC3-H-1 myocytes, where they had earlier reported that pertussis toxin inhibits DNA synthesis and glucose uptake promoted by insulin [10]. Similar findings have been reported using adipocytes [11][12][13]19]. It is also reported that in hepatocyte membranes, insulin attenuates the pertussis-toxin sensitivity of a 40-kDa Gi-like protein [20,21], suggesting that the insulin-bound insR activates the pertussis-toxin-sensitive G protein.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Lutterel et al [18] found that insulin promotes guanine nucleotide-binding to the membranes of BC3-H-1 myocytes, where they had earlier reported that pertussis toxin inhibits DNA synthesis and glucose uptake promoted by insulin [10]. Similar findings have been reported using adipocytes [11][12][13]19]. It is also reported that in hepatocyte membranes, insulin attenuates the pertussis-toxin sensitivity of a 40-kDa Gi-like protein [20,21], suggesting that the insulin-bound insR activates the pertussis-toxin-sensitive G protein.…”
Section: Introductionsupporting
confidence: 63%
“…Receptors activate G proteins by stimulating the GDP/GTP exchange of G proteins. It has been reported that pertussis toxin inhibits insulin-stimulated metabolic action as well as mitogenic action in intact cells [9][10][11][12][13][14]. Pertussis toxin ADPribosylates Gt, Gi, and Go and uncouples them from receptors [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years evidence has accumulated which suggests that insulin receptor signalling may involve coupling to GTP-binding proteins [1][2][3][4][5][6][7]. This view is mainly supported by the effects of cholera and pertussis toxin on insulin action.…”
Section: Introductionmentioning
confidence: 99%
“…This view is mainly supported by the effects of cholera and pertussis toxin on insulin action. Thus, cholera toxin was found to modify insulin signalling in the liver [1] and in the heart [7], whereas pertussis toxin attenuates the activation of hexose transport and the generation of inositolglycan mediators in BC3H-I myocytes [3], and the antilipolytic activity of insulin in adipocytes [2]. More recently it was found that insulin increases GTP-binding to plasma membranes from fat and muscle cells [8,9] and that this binding occurs at a 40/41 kDa membrane protein very similar or identical to G~ [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Cholera toxin, which ADP-ribosylates primarily the stimulatory G-proteins (G,), has been shown to increase insulin-stimulated protein synthesis [4], and insulin inhibits stimulation of adenylate cyclase by this toxin [5]. Pertussis toxin, which ADP-ribosylates the inhibitory type of G-proteins (Gi) and G,, inhibits a number of insulin-stimulated cellular events such as glucose transport [6] and its metabolism [7], protein synthesis [4], and activation of cyclic AMP phosphodiesterase [8]. Interestingly, insulin inhibits pertussis toxin catalyzed ADP-ribosylation of Gi [9] and this toxin also attenuates insulin-induced inhibition of adenyl cyclase [8].…”
Section: Introductionmentioning
confidence: 99%